2022
DOI: 10.1002/dta.3386
|View full text |Cite
|
Sign up to set email alerts
|

Phospholipid metabolites of GHB as potential biomarkers in whole blood: Synthesis, analytics, and in vitro formation of homolog 16:0/18:1

Abstract: Gamma-hydroxybutyric acid (GHB) is a common drug of abuse, and the detection of a consumption or administration is a longstanding research objective in clinical and forensic toxicology. However, until now, the short detection window of GHB could not be enlarged by the use of GHB metabolites. Therefore, new biomarkers for the detection of a GHB intake are needed. In analogy to phosphatidylethanols as longtime biomarkers of ethanol, phospholipids with GHB might represent a promising compound class. While the ava… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 62 publications
0
3
0
Order By: Relevance
“…In addition, phosphatidyl-GHB (16:0/18:1) has a concentration-dependent and time-dependent GHB exposure and it remains at high levels after 72 h of GHB exposure, but it has been studied relatively low. The results of GHB biomarker studies have demonstrated the correct direction of indirect identification of GHB [73] , which can effectively solve the problems of short GHB identification window and differentiation between endogenous and exogenous GHB. Due to the limitations of the study, the statistical relationship between GHB metabolism-related biomarkers and GHB exposure has not been fully established, and the quantitative identification of GHB exposure by biomarkers is still not possible, and further research is needed.…”
Section: Enhancement Of Ghb By Ghb Metabolism-related Biomarker Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, phosphatidyl-GHB (16:0/18:1) has a concentration-dependent and time-dependent GHB exposure and it remains at high levels after 72 h of GHB exposure, but it has been studied relatively low. The results of GHB biomarker studies have demonstrated the correct direction of indirect identification of GHB [73] , which can effectively solve the problems of short GHB identification window and differentiation between endogenous and exogenous GHB. Due to the limitations of the study, the statistical relationship between GHB metabolism-related biomarkers and GHB exposure has not been fully established, and the quantitative identification of GHB exposure by biomarkers is still not possible, and further research is needed.…”
Section: Enhancement Of Ghb By Ghb Metabolism-related Biomarker Studiesmentioning
confidence: 99%
“…Steuer et al [70,71] used an untargeted metabolomics approach to study GHB conjugates and found that urinary concentrations of GHB-glutamate, GHB-glycine, GHB-taurine and GHB-carnitine increased significantly after 4.5 h of GHB exposure, but decreased rapidly after 8 h. In 2022, Kraemer et al [72] used liquid chromatography with tandem mass spectrometry in negative ion mode for blood or blood spot samples, and found that 4-Palmitoyloxy butyrate, which is the palmitic ester of GHB (GHB-Pal) could be detected in plasma or serum at high GHB concentrations (>4 µg/ml), but GHB-Pal was found to be highly variable individually and susceptible to sodium fluoride and degradation. Recently, Thimm et al [73] found that Phoshatidyl-GHB (P-GHB) was highly GHB concentration-dependent in blood, and that when 50 mM GHB was added to the blood, P-GHB concentrations continued to increase until peak concentrations occurred after 72 h (17.4 µg/ ml). However, as this is only an exploratory study, further research is needed.…”
Section: Xenobiotic Metabolism Pathway Of Ghbmentioning
confidence: 99%
“…Fatty acid (FA) esters and phospholipid metabolites, 34 well‐known metabolites, for example, for ethanol, were recently also considered as possible GHB metabolites. For that purpose, Kraemer et al synthesized GHB‐palmitic acid ester (GHB C16) and could detect this GHB conjugate as well as possible FA esters with myristic acid (GHB C14), stearic acid (GHB C18), and oleic acid (GHB C18:1) in four blood samples and also phospholipid metabolite (16:0/18:1) have recently been described 34 . However, to date, the expected concentration levels of all these GHB conjugates in GHB positive and negative cases and their actual ability to extend the detection window of GHB have not been systematically investigated.…”
Section: Introductionmentioning
confidence: 99%
“…33 Untargeted metabolome screening approaches on urine and serum samples from a controlled GHB administration study in humans identified a number of novel conjugates of GHB with carnitine, the amino acids (AA) glycine, glutamate, and taurine, the carbohydrate pentose, and some interesting compounds (U3, U4, and U16) unknown to date, next to changes in endogenous compounds. 23,25 Fatty acid (FA) esters and phospholipid metabolites, 34 well-known metabolites, for example, for ethanol, were recently also considered as possible GHB metabolites. For that purpose, Kraemer et al synthesized GHB-palmitic acid ester (GHB C16) and could detect this GHB conjugate as well as possible FA esters with myristic acid (GHB C14), stearic acid (GHB C18), and oleic acid (GHB C18:1) in four blood samples and also phospholipid metabolite (16:0/18:1) have recently been described.…”
mentioning
confidence: 99%
See 1 more Smart Citation